Books of Martyrs: Example and Imitation in Europe and Japan, 1597–1650 - Brockey, Liam Matthew (The catholic historical review, 2017)
The early modern period witnessed a revival of the cult of martyrs in Western Christendom due to the bloody struggles over religion within and beyond Europe. One of the most important sources for this renewal within Catholicism was the period of persecution of clergy and laity in Japan which began in 1597. Despite the horrors found in the accounts that circulated in Europe and its colonial empires, the profusion of texts and images inspired still other priests and friars to seek missionary assignments in Japan for the express purpose of obtaining martyrdom.